Efisiensi Pajak dalam Pemilihan Bentuk Badan Usaha UMKM: Studi Perbandingan CV dan PT serta Peran Strategis Notaris - Hartono, Honggo; Silalahi, Hermanto (Universitas Katolik Widya Karya Malang, 2025)
The choice of business entity by micro, small, and medium enterprises (UMKM) carries significant fiscal implications, as it determines the applicable tax regime. Generally, the Commanditaire Vennootschap (CV) is considered more tax-efficient than a Limited Liability Company (Perseroan Terbatas/PT), as profits withdrawn as prives are not subject to double taxation. However, under Indonesia's progressive Individual Income Tax (PPh OP) system, the tax burden on prive can exceed the final 10% tax rate on dividends distributed by PTs, particularly at higher income brackets. This study employs a qualitative approach through literature review and tax burden simulation comparing CV and PT. The findings reveal that the fiscal efficiency of CVs largely depends on the owner's personal income tax rate. The results emphasize the strategic role of Notaries as both legal and fiscal advisors in guiding UMKM to select the most appropriate business form. This research contributes to the tax policy discourse and strengthens the understanding of the Notary's role in fostering UMKM compliance and sustainability.